The approaching end of the age viewed in the light of history, prophecy and science - Guinness, Henry Grattan, 1835-1910; Horne, E.H. (London, UK Morgan and Scott, 1918)
Includes bibliographical references and index.
Brethren writer. Donated by Mrs F.F. Hunter.
Keywords: Eschatology